KEMAMPUAN PASIEN GANGGUAN JIWA DALAM PEMENUHAN PERAWATAN DIRI DI WILAYAH KERJA PUSKESMAS NGRONGGOT KABUPATEN NGANJUK - Sulistyorini, Ariani; Setyawati, Deva Octa (STIKES dan AKZI Karya Husada Kediri, 2024)
Self-care is an action to maintain personal hygiene, both physical and psychological. Indicators of self-care ability in patients with mental health problems, namely the patient can say, prepare and practice personal hygiene (bathing, brushing teeth, and shampooing), dressing up, eating, and defecating properly and correctly. The research aims to determine the ability of mental disorder patients to fulfill self-care in the working area of ​​the Ngronggot Community Health Center, Nganjuk Regency. Descriptive research design. The population of all mental disorder patients in the Ngronggot Community Health Center Working Area, Nganjuk Regency totaled 103 respondents, a sample of 30 respondents using a purposive sampling technique. The research was conducted from March 20 – April 3, 2023. The research variable is the ability of mental disorder patients to fulfill self-care. Research instruments are questionnaires and observations. The data is analyzed using a percentage formula and interpreted quantitatively. The research results of 30 respondents found that all respondents, namely 30 respondents (100%) experienced an inability to fulfill self-care. The patient's failure to fulfill self-care is influenced by the disorders experienced by mental disorder patients, namely cognitive, memory, volitional, and psychomotor disorders. This is also supported by factors such as gender, occupation, whether they have ever been treated in a mental hospital, how long they have suffered, and how many times they have been treated. It is hoped that respondents who experience an inability to care for themselves will train themselves in self-care, and their families will be active in reminding and increasing the ability of mental disorder patients to fulfill better self-care.